(untitled) (Journal of the College of Education for Women, 2019)
The research aims for the study about Ibn Tulun’s personal and scientific biography to thescholar, scientist and historian Ibn Tulun Shams Id- Din Mohammad Ibn Ali al-Dimashqi al-Salihi (953 A.H. / 1546 A.D.) Ibn Tulun was a prominent Muslim historian in Blad al-Sham.At the first deals with Ibn Tulun’s personal biography, author’s name, Lineage, andnickname, his nativity; his upbringing, and edification, his moral character, Finally, his death.As to Ibn Tulun’s scientific biography, at the first deals with his initiation into educationand learning , sheds light on his tutors and his authorities , scientific stations and travels , hisscholarly status , and Ibn Tulun’s alumni or his students .